Improving Control Performance in DC Micro-Grids with Distributed Generations - Weilin Li; Huimin Li; Min Luo; Yunfei Zhang (Institute of Advanced Engineering and Science, 2012)
DC micro-grids are attracting more and more attention due to their capability to lead to more efficient integration of distributed generation compared with traditional AC micro-grids. In this paper, a hierarchical control architecture is proposed to improve the control performance of DC micro-grid with distributed generations (DGs), which utilize a global controller (GC) to optimize the overall process and a number of distributed local controllers (LCs) associated with each subsystem. The measurement reliability of each LC is guaranteed by an associated measurement validation module which is developed based on Polynomial Chaos Theory (PCT). The system efficiency and robust is counted in the design of GC, where synergetic control theory is adopted. Numerical simulations have been done to verify the proposed method, and the simulation results show good consistency with theoretical analysis.